2016
DOI: 10.1016/j.immuni.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA-183-96-182 Cluster Promotes T Helper 17 Cell Pathogenicity by Negatively Regulating Transcription Factor Foxo1 Expression

Abstract: Summary T helper 17 (Th17) cells are key players in autoimmune diseases. However, the roles of non-coding RNAs in Th17 cell development and function are largely unknown. We found that deletion of the endoribonuclease Dicer1 gene specifically in Th17 cells protected mice from experimental autoimmune encephalomyelitis. We found that the Dicer1-regulated microRNA (miR)-183-96-182 cluster (miR-183C) was highly expressed in Th17 cells and was induced by cytokine IL-6-STAT3 signaling. miR-183C expression enhanced pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 45 publications
7
165
0
4
Order By: Relevance
“…2-5) and organismic levels [13]. Target prediction analyses and experimental data from other organ systems have shown that miR-183/96/182 regulates hundreds of downstream target genes [7, 8, 18]; therefore, we predict that DAP12 and Nox2 are not the only functional targets of miR-183/96/182 in Mϕ and neutrophils to mediate its functions. We further predict that miR-183/96/182 may modulate other aspects of Mϕ and neutrophil functions, e.g., migration and chemotaxis, through targeting multiple genes involved in cytoskeletal reorganization [unpubl.…”
Section: Discussionmentioning
confidence: 90%
“…2-5) and organismic levels [13]. Target prediction analyses and experimental data from other organ systems have shown that miR-183/96/182 regulates hundreds of downstream target genes [7, 8, 18]; therefore, we predict that DAP12 and Nox2 are not the only functional targets of miR-183/96/182 in Mϕ and neutrophils to mediate its functions. We further predict that miR-183/96/182 may modulate other aspects of Mϕ and neutrophil functions, e.g., migration and chemotaxis, through targeting multiple genes involved in cytoskeletal reorganization [unpubl.…”
Section: Discussionmentioning
confidence: 90%
“…to B6 mice on the day of immunization. At 13 d postimmunization, uveitogenic T cells were isolated and restimulated with IRBP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and APCs under nonpolarizing conditions in the presence of Ag. As shown in Fig.…”
Section: Cl097-stimulated Dcs Enhance Irbp-specific Th17 Responses Anmentioning
confidence: 99%
“…IL-23R signaling is required for the pathogenicity of Th17 cells in vivo (6,7). The development of pathogenic Th17 cells is orchestrated by a complex network of signaling pathways and transcriptional regulators in T cells (8,9). Although the involvement of T cell-intrinsic pathways has been studied extensively, how pathogenic Th17 development is shaped by extrinsic signals derived from the innate immune system is relatively less understood.…”
mentioning
confidence: 99%
“…Many have suggested that the balance between Th1, Th2, and Th 17 could play a role in the CF disease (31). It has been established that Th17 is known to be a key player in autoimmune diseases (40). In addition, the authors showed that Th17 is regulated by miR-183C via inhibition of Foxo1 (40).…”
Section: Cftr and Hyperinflammationmentioning
confidence: 99%
“…It has been established that Th17 is known to be a key player in autoimmune diseases (40). In addition, the authors showed that Th17 is regulated by miR-183C via inhibition of Foxo1 (40). For a long time, it has been thought that CFTR mutations in epithelia cells have an indirect effect on the immune system which causes the inflammation in the lungs, because of the colonization of bacteria in the lungs like P. aeruginosa, Burkholderia cenocepacia, and Mycobacterium abscessus which causes the infections in the CF patients (31).…”
Section: Cftr and Hyperinflammationmentioning
confidence: 99%